2009
DOI: 10.1111/j.1472-4642.2008.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of alien plant distribution at multiple spatial scales in a large national park: implications for ecology, management and monitoring

Abstract: Aim Spatial scale is critical for understanding and managing biological invasions. In providing direction to managing alien plant invasions, much emphasis is placed on collecting spatially explicit data. However, insufficient thought is often given to how the data are to be used, frequently resulting in the incompatibility of the data for different uses. This paper explores the role of spatial scale in interpreting, managing and monitoring alien plant invasions in a large protected area.Location Kruger Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 36 publications
(65 reference statements)
0
69
0
1
Order By: Relevance
“…In contrast, savanna habitats in Africa and Asia are mostly invaded by Neotropical woody plants, such as Lantana camara (L.) and Chromolaena odorata (L.) King and Robinson (Foxcroft et al 2009(Foxcroft et al , 2010. These woody invaders differ from the invasions by grasses in their effect on the fire regime.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, savanna habitats in Africa and Asia are mostly invaded by Neotropical woody plants, such as Lantana camara (L.) and Chromolaena odorata (L.) King and Robinson (Foxcroft et al 2009(Foxcroft et al , 2010. These woody invaders differ from the invasions by grasses in their effect on the fire regime.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, several techniques involving species distribution models would allow the incorporation of several ecological parameters (Engler et al 2004;Guisan and Thuiller 2005). In addition, refining the geographic grain and extent of the model is very important to both implementation of the management plan and field-level activities (Foxcroft et al 2009;Osawa et al 2011;Akasaka et al 2012). In the present study, we used the 5-km mesh on a prefectural scale (i.e., local government) as the unit of analysis.…”
Section: Estimation Of Risk Based On Limited Informationmentioning
confidence: 99%
“…Different spatial scales may explain differing results between studies (Powell et al 2013), and greater insights can be drawn when analyzing data on a finer scale (Wiens 1989). For instance, Foxcroft et al (2009) found Kruger National Park in South Africa to be highly invaded when assessed at a quaternarywatershed level, but the 0.1 by 0.1 km scale revealed finer details, including more significant associations, such as that between the invader, largeleaf lantana [Lantana camara L.], and rivers. These associations may have important management implications but are lost at coarser scales.…”
Section: Herbarium Recordsmentioning
confidence: 99%
“…This would allow scaling up (Pyšek and Hulme 2005), which may be useful when comparing the findings with other data collected at a coarser scale (Foxcroft et al 2009). However, based on the studies cited earlier (see also Table 1) and the present capacity of herbarium collection campaigns to include GPS data, we consider quadrats of 10 by 10 km assessed annually for presence/absence to be a good compromise to report abundance in standard invasive species curves.…”
Section: Herbarium Recordsmentioning
confidence: 99%